EKSPOSE INFO PRODUK PENYANDANG DISABILITAS KOTA YOGYAKARTA - Utami Hayati; Uning Lestari; Yuliana rachmawati (Jurnal SCRIPT, 2015)
Along with the development of technology in today's demanding applications to enable people to do something. Various techniques, methods and new approaches made to enhance and develop the technology specifically to get the right information, quickly and accurately. Limitations with disibalitas in the marketing of their products can be handled with in her system information Exposure Product Info Disability Yogyakarta. It can help disseminate their products geographically over the internet. Here the creative persons with disabilities are given the opportunity to market their products more widely. In this application contains the process of buying and selling handicraft products of persons with disabilities who have the creativity to make crafts such, with this same practice is expected to assist persons with disabilities to promote and sell their crafts. And the wider community will know that a lot of people with disabilities can make crafts that quality is not inferior of handicrafts made by normal people in general. With the system information of this website, it will increase their sales turnover or in dealing with economic problems. By expanding marketing through this website.